Ang II Promotes Cardiac Autophagy and Hypertrophy via Orai1/STIM1 - Zheng, Chang-Bo; Gao, Wen-Cong; Xie, Mingxu; Li, Zhichao; Ma, Xin; Song, Wencong; Luo, Dan; Huang, Yongxiang; Yang, Jichen; Zhang, Peng; Huang, Yu; Yang, Weimin; et al. (Frontiers in Pharmacology, 2021)
The pathophysiology of cardiac hypertrophy is complex and multifactorial. Both the store-operated Ca2+ entry (SOCE) and excessive autophagy are the major causative factors for pathological cardiac hypertrophy. However, it is unclear whether these two causative factors are interdependent. In this study, we examined the functional role of SOCE and Orai1 in angiotensin II (Ang II)-induced autophagy and hypertrophy using in vitro neonatal rat cardiomyocytes (NRCMs) and in vivo mouse model, respectively. We show that YM-58483 or SKF-96365 mediated pharmacological inhibition of SOCE, or silencing of Orai1 with Orail-siRNA inhibited Ang II-induced cardiomyocyte autophagy both in vitro and in vivo. Also, the knockdown of Orai1 attenuated Ang II-induced pathological cardiac hypertrophy. Together, these data suggest that Ang II promotes excessive cardiomyocyte autophagy through SOCE/Orai1 which can be the prime contributing factors in cardiac hypertrophy.